2018
DOI: 10.3390/ijms19103256
|View full text |Cite
|
Sign up to set email alerts
|

How to Process Sputum Samples and Extract Bacterial DNA for Microbiota Analysis

Abstract: Different steps and conditions for DNA extraction for microbiota analysis in sputum have been reported in the literature. We aimed at testing both dithiothreitol (DTT) and enzymatic treatments of sputum samples and identifying the most suitable DNA extraction technique for the microbiota analysis of sputum. Sputum treatments with and without DTT were compared in terms of their median levels and the coefficient of variation between replicates of both DNA extraction yield and real-time PCR for the 16S rRNA gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…In this study, although post-sequencing analysis revealed comparable performances between the BT and ZB kits across multiple types of respiratory samples, the impact of sample type on other DNA extraction methods requires further investigation. For example, between-kit differences appear to be magnified in gut samples [40, 45] and reduced in respiratory samples [42, 43]. Nevertheless, both BT and ZB kits performed similarly in terms of extracting specific bacteria in the mock community and showed differences in bacterial compositions and diversity metrics between different respiratory sites (Tables 2 and 3), and have therefore validated our previous reports [2, 1517].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, although post-sequencing analysis revealed comparable performances between the BT and ZB kits across multiple types of respiratory samples, the impact of sample type on other DNA extraction methods requires further investigation. For example, between-kit differences appear to be magnified in gut samples [40, 45] and reduced in respiratory samples [42, 43]. Nevertheless, both BT and ZB kits performed similarly in terms of extracting specific bacteria in the mock community and showed differences in bacterial compositions and diversity metrics between different respiratory sites (Tables 2 and 3), and have therefore validated our previous reports [2, 1517].…”
Section: Discussionsupporting
confidence: 84%
“…This normalization appeared to eliminate between-kit differences in the number of 16S rRNA sequences (Fig 3B). Studies evaluating kit effects on bacterial diversity typically focus on the differences observed in the concentration of 16S rRNA copies detected via quantitative PCR without paying much attention to the actual number of 16S rRNA sequences recovered [40, 42]. Furthermore, the contribution of unnormalized DNA concentrations to the observed microbiota profile differences between kits needs to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Although standards have been set for the assessment of the stool microbiome, these standards have not been assessed for small intestinal fluid assessment. Mucous in general is a viscous fluid that can trap bacteria in its matrix and previous studies performed with sputum samples have shown that treating this viscosity has an impact on the microbial assessment [5,16]. However, until now, no studies have investigated the impact on microbial assessment and DNA recovery in aspirates collected from small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…The existing sputum liquefaction schemes include the following methods: i) standard N-acetyl-l-cysteine treatment and digestion with 2% NaOH and decontamination; ii) NaOCl liquefaction and sedimentation; iii) chitin solution liquefaction; iv) the use of sputum and an equal volume of phosphate buffer containing 1 g L −1 protease K to liquefy sputum; and v) classical dithiothreitol (DTT) liquefaction, in which a chitin solution homogenizes the mucus sputum more quickly than the N-acetyl-l-cysteine and NaOCl methods. [47][48][49] With the advancement of automated processing, a portable, low-power preprocessing device can perform all of the required steps for sputum preprocessing, including liquefaction, homogenization, dissolution, and inactivation. [50]…”
Section: Sputummentioning
confidence: 99%